PENGARUH PARTISIPASI MASYARAKAT, KAPASITAS APARATUR GAMPONG DAN PENGAWASAN BADAN PERMUSYAWARATAN GAMPONG TERHADAP KINERJA PENGELOLAAN ALOKASI DANA GAMPONG (STUDI PADA KECAMATAN GEUMPANG, MANE, DAN TANGSE KABUPATEN PIDIE) - Sari, Rizky Ananda; Ningsih, Endang Surasetyo (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This study aims to examine the effect of community participation, the capacity of the village apparatus, and the supervision of the village consultative department on the performance of village fund allocation management in Geumpang, Mane and Tangse sub-districts of Pidie District. The primary data used is obtained from closed questionnaire using Likert scale. There are 185 samples of data that become the object of research. Hypotheses were tested using multiple linear regression analysis. The results showed that simultaneously the variables of community participation, the capacity of the village apparatus, and the supervision of the village consultative department had an effect on the performance of the village fund allocation management. Partially, the result of the research indicates that (1) the participation of the community influences the performance of the management of the village fund allocation, (2) the capacity of the village apparatus affects the management performance of the village fund allocation and (3) the supervision of the village consultative department affects the performance of the village fund allocation management.